Migraine In Systemic Lupus Erythematosus in Rheumatological outpatients unit - Shaker, Ameer (AL-Kindy College Medical Journal, 2019)
Background: Migraine is common in systemic lupus erythematosus.It is a significant source of patient disability.Objective: To determine the rate of migraine in patients with systemic lupus erythematosus, to assess migraine type, severity, and the association between migraine and patient’s characteristics.Type of the study: Cross-sectional study.Methods: 100 subjected were recruited and divided into two groups; fifty patients with the diagnosis of systemic lupus erythematosus were recruited from the Rheumatologic department of medicine,and another 50 normal subjects, then complete medical and drugs history were taken from them.Results: Fifty patients completed the questionnaire. Thirty percent of systemic lupus erythematosus patients and 12% of normal subjects had migraine. Of the patients with migraine 80%, 13.3% and 6.7% met criteria for migraine without aura, migraine with aura and retinal migraine respectively. The moderately severe migraine was commonly observed (53.3%). There were significant associations between migraine and systemic lupus erythematosus patients who have Raynaud’s phenomenon, and cardiolipin antibodies.There were no statistically significant associations between migraine, systemic lupus erythematosus duration and patient’s age,sex, and anti-dsDNA.Conclusions:A high rate of migraine in patients with systemic lupus erythematosus.Migraine associated with Raynaud’s phenomenon, and cardiolipin antibodies.